Pengaruh Penggunaan Electronics Audit dan Penerapan International Standard on Auditing terhadap Efektivitas Kerja Auditor dalam Proses Audit Laporan Keuangan - Lim Hendra (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2018)
The purpose of this research is to determine how the influence of electronic audit that used by the auditor to the effectiveness of auditor performance in the process of financial reporting audit. International Standard on Auditing is required by regulation to implemented by the audit firm in the process of financial reporting audit, effectiveness of audit and process of audit is depend on the willingness of the auditor to implemented the professional standard that already established by the professional association of audit (Indonesia Institute of Public Accountant / IAPI). Those matters are the reasons of this research. The kind of research is descriptive. This research used primary data from questionnaires that distributed to 40 auditors in audit firm in Jakarta that have used electronic audit in the process of financial statement audit. Data was analyzed using multiple regression analysis and did hypothesis analysis with partial test and simultaneous by SPSS version 17.The result of this research showed electronic audit that already implemented International Standard on Auditingsignificantly influence the effectiveness of auditor performance in process of financial reporting audit. The conclusion is electronic audit help the auditor the process of risk assessment procedures, how to respond the risk of audit, how to capture the risks of segregation on duties, and finally implemented of International Standard on Auditing in the process of financial reporting audit.